पाणिनेरष्टाध्यायीजाम्बवतीविजयग्रन्थयोः समीक्षणम् - Gautam, Nagendra (Haimaprabha, 2026)
This article describes in detail the qualities and characteristics of the two eight-chapter poems, Jambavati and Vijaya, composed by Pāṇini. An attempt has been made here to demonstrate the fact that Panini was not only a supreme grammar teacher, but also a skilled and accomplished hand in the science of poetry. Panini, based on the fourteen Sutras such as ’Aiun’ obtained by the grace of Maheshwara, begins the grammar from the first Mangalacharana Sutra ’Vrddhiradaich’ with the seal of retraction and ends the eighth chapter in the Sutra "A A" In the eighth chapter, the fourteen precepts are also discussed in detail. Some also believe that the Dhatupatha, the Ganapatha and the Linganushasana were compiled by Panini, yet the grammar is Panini. As stated in the Mahabhashya, ’Almost Panini’s grammar is authentic." The most famous Sanskrit grammar, the Ashtadhyayika, defines the rules of form and composition of language in a very scientific manner. The Ashtadhyayana is not only the pillar of Sanskrit grammar, but also a philosophical mirror of philosophy, linguistics and logic The commentator, describing the grammar, wrote that it is "grammar in the characteristics of the objectives." The house of Satrajit was being decorated. Meanwhile, to refute the blasphemy, Krishna himself entered the forest region and began to search for the gem Rama, I was your servant in the past." Knowing this, he offered the jewel. Above He gave his daughter Jāmbavatī, who was equal to a jewel, as an offering to Lord Kṛṣṇa. In this poem divine might, purity of truth, humility of devotion and protection of religion are described in a wonderful way In conclusion, therefore, the fact is revealed that Maharishi Panini, the author of the Ashtadhyayika Grammar, is the same wise author of the Jambavati Vijayakavya, and the decision is given in the conclusion of the article.